Role of Livestock and Veterinary Services in Employment and Poverty Reduction in Afghanistan - Samadi, Assadullah (Journal of Natural Sciences – Kabul University, 2020)
Afghanistan is an agricultural country, with a large portion of its population employed in agriculture and livestock industries. Livestock and veterinary services play critical roles in rural development, employment, and poverty reduction in Afghanistan. Despite having 35 million people and millions of animals and poultry, veterinary services are insufficient and cannot meet the basic needs of society. As a result, both infectious and non-infectious diseases continuously threaten animal life and production, directly and indirectly impacting the livelihood and economy of low-income rural families, many of whom rely heavily on their animals and animal products for income. This article discusses the role of livestock and veterinary services in employment generation and poverty reduction.